THE IMPACT OF EDUCATION ON REGIONAL ECONOMIC PERFORMANCE IN INDONESIA - Pratita Vajar Kusuma (International Journal of Economics, Business and Accounting Research (IJEBAR), 2020)
The study aims to investigate the impact of education to regional economic performance. The study utilizes a panel dataset of 30 provinces in Indonesia over the period 2005–2015. The estimation result shows that primary education level, that has become universal attribute to Indonesian, is not statistically significant to regional performance. In contrast, there is a positive and significant evidence of the impact of secondary education and tertiary education levels to the economic performance. Furthermore, we also employ a descriptive statistic to the annual labor survey dataset to gain a deeper understanding on the impact of education to the regional economy through the response of Indonesia’s labor market. The results reveal that there are shifts in the structure of labor force due to change on labor’s education attainment. Also, looking at the wage gap between the education levels and the time needed to find a job, we find that there is a subtle evidence of skill mismatched in the labor market. Keywords: Education, regional economics, labor market, wage gap